2003
DOI: 10.1002/hup.538
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of acute effects of single doses of fexofenadine, olopatadine, d‐chlorpheniramine and placebo on psychomotor function in healthy volunteers

Abstract: Since most classical (first-generation) antihistamines have undesirable sedative effects on the central nervous system (CNS), newer (second-generation) antihistamines have been developed to relieve the sedative effects and to improve the patient's quality of life. However, the psychomotor profiles of second-generation antihistamines are not fully elucidated. In this randomized, double-blind, crossover study, the acute effects of single doses of second-generation antihistamines, fexofenadine (120 mg) and olopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 35 publications
4
39
0
1
Order By: Relevance
“…The half-life of chlorpheniramine is approximately 28 h (range 19-43 h) and maximum plasma concentrations are reached at 2.8 h (range 2-4 h) after oral doses (Huang et al, 1982;Paton and Webster, 1985). Two studies have shown that single oral doses of 4 mg chlorpheniramine produced significant performance impairment, which was most pronounced shortly after t max (Kamei et al, 2003;Witek et al, 1995). Yet, in a third study performance was significantly impaired only at 1.5 h after drug administration (Clarke and Nicholson, 1978).…”
Section: Introductionmentioning
confidence: 95%
“…The half-life of chlorpheniramine is approximately 28 h (range 19-43 h) and maximum plasma concentrations are reached at 2.8 h (range 2-4 h) after oral doses (Huang et al, 1982;Paton and Webster, 1985). Two studies have shown that single oral doses of 4 mg chlorpheniramine produced significant performance impairment, which was most pronounced shortly after t max (Kamei et al, 2003;Witek et al, 1995). Yet, in a third study performance was significantly impaired only at 1.5 h after drug administration (Clarke and Nicholson, 1978).…”
Section: Introductionmentioning
confidence: 95%
“…However, some previous studies have described that olopatadine hydrochloride induced CNS side effects, in spite of the fact that it is a second-generation nonse-dating antihistamine 13. Furthermore, 10 mg olopatadine hydrochloride was also reported to cause a decrease in activity, although it did not affect psychomotor/cognitive performance 20. Therefore, we suggest that treatment with 5 mg olopatadine hydrochloride is beneficial and provides long-lasting symptom relief for CU patients, with no or fewer CNS side effects such as drowsiness or sedation.…”
Section: Discussionmentioning
confidence: 93%
“…Olopatadine is currently approved in Japan for treatment of symptoms of allergic rhinitis, chronic urticaria, at a total daily oral dose of 10 mg, and in the United States and Europe, it is approved only as an ophthalmic solution for the treatment of seasonal allergic conjunctivitis [22]. It is approved for use in adults and children aged 3 years and older [23].…”
Section: Olopatadine Hydrochloridementioning
confidence: 99%
“…This comfort likely is a consequence of olopatadine's more compatible pH 23 and possibly its low intrinsic ocular membrane surface activity [18]. The release of lactate dehydrogenase (LDH; an intracellular constituent of conjunctival mast cells) was used as an evaluation tool, although its clinical relevance is unclear.…”
Section: Comfort Studiesmentioning
confidence: 99%